EDUCATION AND FREEDOM IN FREDERICK DOUGLASS’S - Ahouangansi, SÈNAKPON RAOUL (My University, 2018)
The inalienable rights related to life, liberty and pursuit of happiness highly advocated by the American Declaration of Independence fail to bring hopes to fruition. They prove restricted in their implementation due to circumstances dictated by race and the institution of slavery. Blacks of every age suffer extremist hardships which deprive them from the key to success: education. Frederick Douglass, a fugitive slave and fiercely dedicated to abolitionist principles and goals reveals in his book Narrative of the Life of Frederick Douglass, An American Slave, his heroic journey from slavery to freedom while experiencing education as a sine qua non condition. In light of this, the present essay quests racism as an American social plague and demonstrates how education saves African-Americans from the yoke of a certain dehumanization.
Keywords: right; race; slavery; freedom; education